(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2008)
The data about recent composition of phytoplankton dominant complex of Eastern Sivash (Ukraine) together with the analysis of its changing from the beginning of the XXth century up to the recent time are presented. It was shown the changing of phytoplankton communities composition from euhalobic-polyhalobic, euhalobic and mesohalobic at the beginning and the middle time of the XXth century up to oligo-mesohalobic ones at the beginning of the XXI century. Such tendency is associated with the modern data about desalination process of Eastern Sivash at the recent time.